A Bibliometric Analysis and Global Trends in Fascioliasis Research: A Neglected Tropical Disease - Tauseef Ahmad; Muhammad Imran; Kabir Ahmad; Muhammad Khan; Mukhtiar Baig; Rami H. Al-Rifai; Basem Al-Omari (Animals, 2021)
Background: Fascioliasis is a zoonotic neglected tropical disease caused by Fasciola hepatica and F. gigantica. In endemic regions, fascioliasis represents a huge problem in livestock production and significantly threatens public health. The present study was performed to assess the key bibliometric indicators, plot the global research outcome, and strive to find the research frontiers and trends in fascioliasis. Methods: A descriptive bibliometric and visualized study was conducted. The data were extracted from the Web of Science Core Collection (WoSCC) database. The WoSCC was searched using key terms covering a wide range of synonyms related to the causative agent (Fasciola) and the disease (fascioliasis). The database search was performed for the period from the inception of WoSCC until 3 October 2021. The downloaded data were exported into VOSviewer software version 1.6.17 for Windows to construct co-authorship countries, keywords co-occurrence, bibliographic coupling sources, and citation and documents network visualization. Results: A total of 4165 documents were included in this bibliometric analysis. The included documents were published between the years 1913 and 2021 from 116 countries, mainly from the United States of America (USA) (n = 482, 11.6%). The most prolific year was 2018 (n = 108). The journal that attracted the most publications was Veterinary Parasitology (n = 324), while the most productive author in this area was Rondelaud D (n = 156). In terms of total link strength (TLS), the most influential country was Spain (TLS = 236), followed by the USA (TLS = 178). Conclusion: This study is of value for veterinarians, doctors, and researchers to explore insights into research frontiers and trends in research on fascioliasis. The number of publications on fascioliasis has increased over time. Above 35% of publications have been produced by the USA, France, England, and Spain. “Fasciola hepatica” and “cattle” were the most dominant and widely used keywords. Research collaboration should be established among the researchers from developing countries with developed countries to learn new advancements and effective control strategies for fascioliasis.